Solvent-induced self-assembly of hydrogen bonded P4VP-perylenebisimide comb polymer - Narayan, Rekha; Asha, S. K. (Journal of Materials Chemistry C, 2013)
Polymeric supramolecular assemblies were formed when an unsymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) was complexed with poly(4-vinylpyridine) (P4VP) via hydrogen-bonding interaction. The self-assembly behavior of this polymeric supramolecule poly(4-vinylpyridine)-perylenebisimide P4VP(PDP-UPBI)(1.0) was studied in solvents of varying polarity like chloroform (CHCl3) and methylcyclohexane (MCH). Variable concentration and variable temperature proton NMR studies in CDCl3 and deuterated 1,1,2,2-tetrachloroethane (TCE), respectively, revealed the polymeric nature of the perylenebisimide upon complexation and the high thermal stability of the self organized structures in solution. The improved solubility afforded by the complexation enabled variable temperature UV-Vis absorption studies in the non-polar solvent MCH, which indicated the existence of strong face-to-face stacked H-type aggregates. The strong fluorescence quenching in MCH also supported the identification of the nature of aggregates as co-facial H-type. Although the existence of aggregates was not very evident in dilute solutions of chloroform, the fluorescence of the P4VP(PDP-UPBI) 1.0 was quenched compared to that of PDP-UPBI. Thin spin coated films of the complex from chloroform exhibited features of rotationally displaced H-type aggregates characterized by blue shift of absorption maxima and the appearance of a new red shifted peak at 540 nm with weak aggregate emission beyond 600 nm. Morphology analysis of drop cast samples using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the formation of micrometer long multilamellar nanofibers from CHCl3 and two dimensional multilamellar nanosheets upon switching the solvent to MCH.

Supramolecular P4VP-pentadecylphenol naphthatenebisimide comb-polymer: mesoscopic organization and charge transport properties - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A supramolecular comb polymer of pentadecyl phenol (PDP) substituted naphthalenebisimide (PDP-UNBI) with poly(4-vinylpyridine) (P4VP) is reported. The mesoscopic organization within the P4VP(PDP-UNBI), complexes was studied using wide-angle X-ray diffraction (WXRD) technicjues. The packing diagram obtained from the single-crystal XRD analysis of the PDP-UNBI crystals gave a clear picture of the initial arrangement present in self-associated PDP-UNBI alone. Correlating this with the XRD data of the hydrogen-bonded polymer complex provided insight into the probable packing of the P4VP chains within the crystalline lattice of PDP-UNBI leading to a highly ordered lamellar packing. Transmission electron microscopy (TEM) revealed the uniform mesomorphic lamellar structures in the domain range of similar to 5-10 nm. Furthermore, the charge carrier mobility measurements observed from space-charge-limited current (SCLC) measurements demonstrated that transport behaviour of the hydrogen-bonded P4VP(PDP-UNBI) complex (2 x 10(-2) cm(2) V-1 s(-1)) was comparable to that of the crystalline naphthalenebisimide molecule itself (9 x 10(-3) cm(2) V-1 s(-1)), which is a great achievement, since the complex now offers a package of solution-processable n-type semiconductor polymer with mobility equivalent to that of a small crystalline molecule.